Surface modification of sugarcane bagasse cellulose and its effect on mechanical and water absorption properties of sugarcane bagasse cellulose/ HDPE composites - Mulinari, Daniella Regina [UNESP] (2010)
Cellulose fibres from sugarcane bagasse were bleached and modified by zirconium oxychloride in order to improve the mechanical properties of composites with high density polyethylene (HDPE). The mechanical properties of the composites prepared from chemically modified cellulose fibres were found to increase compared to those of bleached fibres. Tensile strengths of the composites showed a decreasing trend with increasing filler content. However, the values for the chemically modified cellulose fibres/HDPE composites at all mixing ratios were found to be higher than that of neat HDPE. Results of water immersion tests showed that the water absorption affected the mechanical properties. The fracture surfaces of the composites were recorded using scanning electron microscopy (SEM). The SEM micrographs revealed that interfacial bonding between the modified filler and the matrix was significantly improved by the fibre modification.